Improved Integrated Business Management for Agriculture and Livestock in Rajik Tourism Village (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The community service program in Rajik Tourism Village involved 50 participants, consisting of farmers and livestock business actors. The program aimed to increase their capacity through strengthening financial literacy, long-term financial planning, creative marketing strategies, and the use of digital technology. The implementation method included pre-implementation, training, and interviews. The results showed that 82% of participants previously had no structured financial recording system, relying only on simple notes or memory. After the training, 90% were able to compile daily cash records, 76% successfully prepared simple income statements, and 68% actively used social media and e-commerce platforms such as WhatsApp Business and Shopee to expand their markets. Long-term financial planning practices were also adopted, with participants setting business goals, allocating 10–20% of profits for emergency funds, and reinvesting in productive assets such as equipment and livestock. These outcomes demonstrate concrete improvements in both managerial and marketing practices. A participatory approach ensured that the solutions developed were adapted to local conditions. Overall, this program contributed to enhancing financial discipline, market access, and business sustainability in Rajik Village, thereby increasing the competitiveness of local products and providing a replicable model for village economic empowerment in other regions.